HUBUNGAN PREEKLAMPSIA/EKLAMPSIA DENGAN KEJADIAN ASFIKSIA BAYI BARU LAHIR DI RUMAH SAKIT ISLAM KLATEN - , SRI WAHYUNI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Preeclampsia is a condition of hypertension accompanied by proteinuria, edema, or both that occurs due to pregnancy after week 20 or sometimes arises earlier when there is a wide hidatiformis at villi khorialis. The risk of neonatal asphyxia is known in many cases of preeclampsia